Key opportunities and challenges for the use of big data in migration research and policy. Issue 3 (27th October 2021) - Franklinos, Lydia H. V.; Parrish, Rebecca; Burns, Rachel; Caflisch, Andrea; Mallick, Bishawjit; Rahman, Taifur; Routsis, Vasileios; López, Ana Sebastián; Tatem, Andrew J.; Trigwell, Robert
Abstract : Migration is one of the defining issues of the 21st century. Better data is required to improve understanding about how and why people are moving, target interventions and support evidence-based migration policy. Big data, defined as large, complex data from diverse sources, is regularly proposed as a solution to help address current gaps in knowledge. The authors participated in a workshop held in London, UK, in July 2019, that brought together experts from the United Nations (UN), humanitarian non-governmental organisations (NGOs), policy and academia to develop a better understanding of how big data could be used for migration research and policy. We identified six key areas regarding the application of big data in migration research and policy: accessing and utilising data; integrating data sources and knowledge; understanding environmental drivers of migration; improving healthcare access for migrant populations; ethical and security concerns around the use of big data; and addressing political narratives. We advocate the need for careful consideration of the challenges faced by the use of big data, as well as increased cross-disciplinary collaborations to advance the use of big data in migration research whilst safeguarding vulnerable migrant communities.